The Other Hidden Curriculum: On Losing Pena and Becoming Educado in a Salvadoran Adult Literacy Program - Esther Prins (Adult Education Research Conference, 2004)
This paper examines how participation in a literacy program in El Salvador helped participants learn new social behaviors (to speak out and to become more well-mannered), and identifies which aspects of the program contributed to these benefits. The study suggests that educators must consider the social dimensions of adult education.